1992
DOI: 10.1111/j.1524-4725.1992.tb02774.x
|View full text |Cite
|
Sign up to set email alerts
|

The Paramedian Scalp Reduction with Posterior Z‐Plasty

Abstract: Combining a large posterior Z-plasty with a paramedian reduction minimizes the slot defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…12,13 A tissue expander is a useful therapeutic alternative to treat wide and visible scarring on the scalp. 14,15 Several authors have reported the use of a V-Y advancement flap, 16 Z plasty, 17 and a hair-bearing flap 18 to treat scar alopecia. Burm and Oh reported the treatment procedure of a wide scar.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A tissue expander is a useful therapeutic alternative to treat wide and visible scarring on the scalp. 14,15 Several authors have reported the use of a V-Y advancement flap, 16 Z plasty, 17 and a hair-bearing flap 18 to treat scar alopecia. Burm and Oh reported the treatment procedure of a wide scar.…”
Section: Discussionmentioning
confidence: 99%